Leadership Communication Approach of the Indonesia Film Censorship Institute to Stimulate a Collaborative Climate - Taufan Teguh Akbari; Rizky Ridho Pratomo (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The incumbent the Film Censorship Institute (LSF) chairman faces a series of challenges inherited from predecessors, necessitating strategic changes to transform LSF into a significant institution characterized by a collective and collegial culture. Consequently, this research seeks to analyze chairman's communication approach and its impact on fostering a collaborative climate. Employing a qualitative research approach, the study utilizes the case study method. Data were gathered through Focus Group Discussions (FGD) and document analysis. Three resource persons participated in the FGD. The findings indicate that the leadership communication approach of the LSF chairman is participatory-democratic. The author contends that leaders play a crucial role in shaping and embodying organizational culture, emphasizing the establishment of a collective and collegial ethos. Leadership communication serves as a catalyst in instilling this culture, encompassing language, behavior, attitude, and character. These elements collectively contribute to fostering a climate of collaboration, as evidenced by programs and policies grounded in collaborative principles.